Variants Within Genes EDIL3 and ADGRB3 are Associated With Divergent Fecal Egg Counts in Katahdin Sheep at Weaning - Becker, Gabrielle M.; Burke, Joan M.; Lewis, Ronald M.; Miller, James E.; Morgan, James L. M.; Rosen, Benjamin D.; Van Tassell, Curtis P.; Notter, David R.; Murdoch, Brenda M. (Frontiers in Genetics, 2022)
Gastrointestinal nematodes (GIN) pose a severe threat to sheep production worldwide. Anthelmintic drug resistance coupled with growing concern regarding potential environmental effects of drug use have demonstrated the necessity of implementing other methods of GIN control. The aim of this study was to test for genetic variants associated with resistance or susceptibility to GIN in Katahdin sheep to improve the current understanding of the genetic mechanisms responsible for host response to GIN. Linear regression and case-control genome-wide association studies were conducted with high density genotype data and cube-root transformed weaning fecal egg counts (tFEC) of 583 Katahdin sheep. The case-control GWAS identified two significant SNPs (P-values 1.49e-08 to 1.01e-08) within introns of the gene adhesion G protein-coupled receptor B3 (ADGRB3) associated with lower fecal egg counts. With linear regression, four significant SNPs (P-values 7.82e-08 to 3.34e-08) were identified within the first intron of the gene EGF-like repeats and discoidin domains 3 (EDIL3). These identified SNPs were in very high linkage disequilibrium (r2 of 0.996 to 1), and animals with alternate homozygous genotypes had significantly higher median weaning tFEC phenotypes compared to all other genotypes. Significant SNPs were queried through public databases to identify putative transcription factor binding site (TFBS) and potential lncRNA differences between reference and alternate alleles. Changes in TFBS were predicted at two SNPs, and one significant SNP was found to be within a predicted lncRNA sequence with greater than 90% similarity to a known lncRNA in the bovine genome. The gene EDIL3 has been described in other species for its roles in the inhibition and resolution of inflammation. Potential changes of EDIL3 expression mediated through lncRNA expression and/or transcription factor binding may impact the overall immune response and reduce the ability of Katahdin sheep to control GIN infection. This study lays the foundation for further research of EDIL3 and ADGRB3 towards understanding genetic mechanisms of susceptibility to GIN, and suggests these SNPs may contribute to genetic strategies for improving parasite resistance traits in sheep.